Bone Mineral Density After Simultaneous Kidney–Pancreas Transplantation: Four Years Follow-up of 57 Recipients - Pereira, S.; Pedroso, S.; Martins, L.; Santos, P.; Almeida, M.; Freitas, C.; Dias, L.; Dores, J.; Almeida, R.; Castro Henriques, A.; Teixeira, M. (Transplantation proceedings, 2010)
Bone disease and an high risk of fractures are major problems in transplantation. Among diabetic patients undergoing simultaneous kidney–pancreas (SKP) transplantation, there are few studies assessing long-term effects on bone mass. The aim of this study was to evaluate bone mineral density (BMD) over 4 years follow-up after SKP transplantation. Fifty-seven patients had 22.8 ± 5.3 years of prior diabetes, 65% were female, and the overall mean age was 24.3 ± 5.93 years. At the time of transplantation, the lumbar spine and femoral neck T-scores were −1.75 ± 1.05 and −1.95 ± 0.73, respectively; 28% of subjects had evidence of osteoporosis. One year after transplantation, 77.6% of patients displayed improved lumbar T-scores to −1.33 ± 0.94 ( P = .044) with stable femoral neck T-scores. Bone densitometry enhanced gradually through the 4 years follow-up: lumbar T-score to −1.04 ± 0.67 ( P = .004) and femoral neck T-score to −1.69 ± 0.49 ( P = .12). At year 4, no osteoporosis cases were detected but 86.7% of patients did not receive steroids in the immunosuppressive regimen. The graft function remained stable (serum creatinine, 1.2 mg/dL; fasting glucose, 87.7 mg/dL). During the follow-up, BMD improved more significantly at cortical sites. Our study reports a reduced prevalence of fractures (8.7%) compared with the literature, which could be related to a steroid-sparing protocol and/or aggressively treatment of osteoporosis.